Cu2+/Cu+ redox-cycling-driven dual-mode sensor for simultaneous monitoring of acetylcholinesterase activity and pesticide exposure - Lai, Sitong; Sun, Kunhui; Wu, Yun; Wu, Xueyuan; Yan, Yiqi; Liu, Guojing; Liu, Xiaoyi; Ge, Yuanyuan; Zeng, Lina; Guo, Ziyu; Wang, Shuhong; Wang, Ping; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe procedural complexity and time-consuming of conventional pesticide residue detection methods in traditional Chinese medicines (TCMs) significantly impeded their application in modern systems. To address this, this study presented an innovative dual-mode sensor driven by Cu2+/Cu+ redox-cycling, which achieved efficient signal transduction from enzyme inhibition to optical response for rapid acetylcholinesterase (AChE) activity and organophosphorus pesticide (OP) residue detection.MethodsThe AB-Cu NPs sensor, a dynamic redox-responsive system, was constructed via coordination-driven assembly of Azo-Bodipy 685 (AB 685) and Cu2+. Initially, Cu2+ quenched the optical signals of AB 685 through photoinduced electron transfer (PET), maintaining an “OFF” state. Upon AChE-catalyzed hydrolysis of acetylthiocholine chloride (ATChCl) to thiocholine (TCh), Cu2+ was reduced to Cu+, thereby activating dual ultraviolet-visible (UV-Vis)/fluorescence (FL) signals (“ON” state). OP residues were quantified by their inhibition of AChE, which blocked Cu2+/Cu+ conversion and suppressed signal generation.ResultsThe sensor exhibited positive sensitivity with detection limits of 0.0327 U/L for AChE activity and 1.72 ng/mL for triazophos, leveraging Cu2+/Cu+ redox-cycling for signal amplification. Notably, the Cu2+/Cu+ valence interconversion coupled enzyme inhibition with probe responsiveness, ensuring the both procedural easily and rapid response.DiscussionThis study developed a portable detection platform based on valence interconversion coupled enzyme inhibition with probe responsiveness. The dual-signal output enhanced reliability and the redox-driven mechanism enabled signal amplification. This advancement provided a real-time, portable and rapid detection for AChE activity and pesticide exposure of TCMs, bridging gaps in agricultural safety and pharmaceutical standardization.